Measuring economic growth in OPEC countries : A panel data approach - Olajide, Johnson Taiwo; Fantola, Jubril Oluwatoyin; Ayansola, Olufemi Aderemi (International Journal of Applied Mathematical Research, 2015)
Most of the developing and under-developed countries have been facing a lot of challenges on the issue of economic growth, despite the fact that they are endowed with both natural and human resources. This study examines the determinants of real per Capita GDP growth in Organization of the Petroleum Exporting Countries (OPEC) using a panel of twelve countries for the period of 1986 and 2010.The pooled Ordinary Least Squares (OLS), Fixed Effect (FE) and Random Effect (RE) models were employed to assess the relationship between CGDP and other economic variables used. The result showed that price level of consumptions (pc) and investment share (ci) are the important factors of CGDP that contribute to the economic growth of OPEC countries. The result also established that exchange rate (Xrat), price of GDP (p), purchasing power parity (ppp) and ci have a positive influence on CGDP. The test statistic revealed that Random Effects Model (REM) estimator is more efficient than OLS and that there is no significance difference between Fixed Effects Model (FEM) and REM estimators.